Management of Nere (Parkia biglobosa) in farmers’ fields in Burkina Faso (West Africa) - Zerbo, G.B.; Millogo, D.; Lompo, D.J.-P.; Ouédraogo, M.; Duminil, J.; Manica, M.; Vinceti, B. (2016)
Parkia biglobosa (Fabaceae-Mimosoideae) is one of the most important and widespread trees in agroforestry systems from Senegal to Uganda. The National Tree Seed Center (CNSF) of Burkina Faso has developed a breeding and improvement program for this multipurpose tree. To better conserve and promote the best reproductive materials for domestication, it is important to understand how farmers perceive and manage the species in their fields. Farmers appear to have an active role in shaping tree species diversity and richness, affecting also the overall spatial distribution, density, and structure of tree populations. We examined some choices made by farmers with regard to species and individuals to be maintained, and practices used to conserve trees